Treatment Patterns, Acute Healthcare Resource Use, and Costs of Patients with Treatment-Resistant Depression Completing Induction Phase of Esketamine in the United States - Lisa Harding; Kruti Joshi; Maryia Zhdanava; Aditi Shah; Arthur Voegel; Cindy Chen; Dominic Pilon (Adis, Springer Healthcare, 2024)
Abstract Background This study aimed to understand treatment patterns, acute healthcare use, and cost patterns among adults with treatment-resistant depression (TRD) who completed induction treatment with esketamine nasal spray in the United States (US). Per label, induction is defined as administration twice a week for 4 weeks, after which maintenance is started on a weekly basis for 4 weeks, and thereafter, patients are treated weekly or bimonthly. Methods Adults with one or more esketamine claim (index date) on or after March 5, 2019 were selected from Optum's de-identified Clinformatics® Data Mart Database (January 2016-June 2022). Before the index date, patients had evidence of TRD and ≥ 12 months of continuous insurance eligibility (baseline period). Patients with eight or more esketamine treatment sessions were included in the main cohort. A subgroup included patients with one or more baseline mental health (MH)-related inpatient (IP) admission or emergency department (ED) visit (i.e., prior acute healthcare users). Treatment patterns were described during the follow-up period (index date until earliest of end of insurance eligibility or data); acute healthcare (i.e., IP and ED) resource use and costs (2021 US dollars) were reported during the baseline and follow-up periods. Results Of the 322 patients in the main cohort, 111 comprised the subgroup of prior acute healthcare users. During the follow-up period, mean time from index date to eighth esketamine session was 73.2 days in the main cohort and 78.8 days in the subgroup (per label, 28 days). Further, 75.2% of the main cohort and 73.9% of the subgroup completed four or more esketamine maintenance sessions following induction. In the main cohort, mean all-cause acute healthcare costs per patient per month (PPPM) decreased from baseline ($837) to follow-up ($770). Similar reductions were observed for mean MH-related acute healthcare costs PPPM (baseline $648, follow-up $577). In the subgroup, mean all-cause acute healthcare costs PPPM also decreased (baseline $2323, follow-up $1423), driven by mean MH-related acute healthcare costs PPPM (baseline $1880, follow-up $1139). Mean all-cause acute healthcare use per ten patients per month remained largely stable from baseline to follow-up in the main cohort (IP days: baseline 2.24, follow-up 2.13; ED visits: baseline 1.33, follow-up 1.45) and decreased in the subgroup (IP days: baseline 6.38, follow-up 4.56; ED visits: baseline 2.58, follow-up 2.41). Trends in mean MH-related acute healthcare use were similar. Conclusion Patients generally required more time than label recommendation to complete esketamine induction treatment, and most went on to have 12 or more esketamine sessions. Completion of induction treatment correlated with reductions in mean all-cause and MH-related acute healthcare costs. Larger reductions were seen in the subgroup of prior acute healthcare users.